Enhanced photocatalytic degradation and H2 evolution performance of NCDs/S-C3N4 S-scheme heterojunction constructed by π-π conjugate self-assembly. (1st July 2022) - Li, Xibao; Luo, Qiuning; Han, Lu; Deng, Fang; Yang, Ya; Dong, Fan
Highlights: Novel 0D/2D NCDs/S-C3 N4 S-scheme heterojunction was prepared by a simple solvent evaporation induced self-assembly method. FT-IR and HRTEM confirmed that NCDs were supported on S-C3 N4 through π-π conjugate interaction. NCDs/S-C3 N4 demonstrated superior photocatalytic performance in degrading organic pollutants and hydrogen evolution. The enhanced photocatalytic activity was attributed to the formation of S-scheme heterojunction with high redox potentials. Abstract: Constructing heterojunction between two semiconductors with matched energy band structure is an effective modification method to obtain excellent photocatalysts. The experimental scheme adopts a simple solvent method to self-assemble nitrogen doped carbon dots (NCDs) on the surface of sulfur doped carbon nitride (S-C3 N4 ) semiconductor through π-π conjugate interaction. Based on this, a novel 0D/2D S-scheme heterojunction NCDs/S-C3 N4 hybrid was successfully prepared. The degradation kinetic constants of NCDs/S-C3 N4 for rhodamine B (RhB) and p-nitrophenol (PNP) reached 0.23522 and 0.01342 min −1, respectively, which were 2.72 and 2.65 times that of S-C3 N4 . The highest photocatalytic hydrogen evolution rate was observed under the simulated sunlight irradiation, which was 2.30 times that of S-C3 N4 . The improvement of photocatalytic performance was mainly based on the formation of the S-scheme heterojunction between S-C3 N4 and NCDs. The effects of internal electric field, π-π conjugate interaction and band bending promoted the photogenerated h + and e − with low redox ability to recombine and retained the beneficial h + and e − with strong redox ability, which contributed to the production of more active species of h + and O2 −, therefore the photocatalytic degradation and hydrogen evolution performance were significantly enhanced.